130 A collaboration between 21 states and territories to prevent child and adolescent injury in the US. (1st September 2016) - Spicer, Rebecca; Allison, Jennifer; Reiney, Erin
Abstract : Background: Over the past three decades, we have generated a strong evidence base of effective interventions to prevent child and adolscent injuries. Nevertheless, a gap persists in the broad implementation of these strategies, and, in the U.S., injury is still the leading cause of death among children and adolescents ages 1–19. Description of the Initiative: The U.S. Maternal and Child Health Bureau, in cooperation with the Children's Safety Network, has just launched the first cohort of 21 states and territories participating in the Child Safety Collaborative Innovation and Improvement Network (CS-CoIIN). In a CoIIN participants support, collaborate and learn from each other and recognised experts to collectively make improvements. With support of the CS-CoIIN, this cohort will apply a quality improvement methodology to pilot, test, and scale up evidence-based interventions at state, and local levels to achieve a measurable impact. Measurement is a critical part of the CoIIN and states will enter monthly data into a virtual data dashboard, including both real-time process and outcome measures. Results: The 21 states and territories participating in the CS-CoIIN represent 47% of the US 0–19 year-old population and account for 43% of their injury deaths. In fall 2015, a consensus process identified the following topic areas: injuries to child passengers and teen drivers; suicide and self-harm; interpersonal violence including bullying; and falls. In December, 2015, states will choose to address up to three of these topics. In September 2016 the CoIIN will be at the end of the first of two years. The proposed presentation will: 1) provide a detailed overview of the injury data that served as the impetus for the initiative; 2) describe the ways states have engaged in CoIIN efforts; 3) present the data collected to-date; and 4) discuss lessons learned. Conclusions: Other countries may benefit from the lessons learned from the groundbreaking work of the CS-CoIIN.